A Wearable Sensory Textile‐Based Clutch with High Blocking Force. Issue 11 (25th September 2019) - Sadeghi, Ali; Mondini, Alessio; Totaro, Massimo; Mazzolai, Barbara; Beccai, Lucia
Abstract : A sensory textile‐based clutch (STBC) activated by vacuum is presented. The STBC is an assembly of two inextensible webbings equipped with 2.3 mm wide rigid bumps fabricated directly on them by a hot embossing technique, and two elastic bands, all air sealed by a silicone elastomer cover. While, in passive mode, the clutch provides low resistance to elongation, upon vacuum, the specular rigid bumps interlock and provide a high withstanding force. The embedded capacitive‐based transducer allows encoding the clutch's elongation, with a position resolution reaching 1.15 mm, owing to a real‐time processing algorithm. The STBC (140 mm × 30 mm × 8 mm) sustains up to 419 N force with an activation pressure of −0.5 atm. The small size of the rigid components and a priming strategy (keeping the pressure at −0.01 atm in disengaged mode) enable response times down to 14 ms for a 115 N blocking force. A preliminary demonstration of a fully worn device shows the potential of the STBC approach for enabling the control of the engagement and disengagement of blocking forces, as well as monitoring of typical parameters of human movement such as knee bending angles, for future developments of light and efficient unpowered exoskeletons. Abstract : The sensory textile‐based clutch (STBC) is a new approach for achieving smart garments in unpowered exoskeletons. It is a flexible, safe, wearable compact device with double fold functionality. When activated by vacuum, the interlocking mechanism sustains up to 419 N. Passive elongation is detected by integrated capacitive sensing and used to retrieve the bending angle of a knee joint.